Efficacy and safety of glycyrrhizin 2.5% eye drops in the treatment of moderate dry eye disease: results from a prospective, open-label pilot study - Burillon C (Clinical Ophthalmology, 2018)
Carole Burillon,1 Frederic Chiambaretta,2 Pierre-Jean Pisella3 1Ophthalmology Department, University Hospital HCL, GH Edouard Herriot, Lyon, France; 2Ophthalmology Department, Clermont-Ferrand University Hospital, Hôpital Gabriel Montpied, Clermont Ferrand, France; 3Ophthalmology Department, Paris Nord Val-de-Seine University Hospitals, Hôpital Bretonneau, Tours, France Background: Dry eye disease (DED) is characterized by a loss of homeostasis of the tear film. It goes along with ocular symptoms, in which ocular surface inflammation and damage play etiological roles. High-mobility group box 1 protein (HMGB1) is a pro-inflammatory protein found in the tear fluid during conjunctivitis, blepharitis and DED. Glycyrrhizin binds to HMGB1, inhibiting cytokine activities, thus potentially improving DED.Aim: To assess the efficacy and tolerance of glycyrrhizin in moderate DED.Methods: Multicenter, open-label, prospective, nonrandomized clinical pilot study of glycyrrhizin 2.5% eye drops twice daily over 28 days in adult patients with moderate DED using standard evaluation parameters.Results: The overall mean age of the 37 patients included was 59.6±19.0 years, 70.3% of the patients were female and 77.0% of the patients had an Oxford score of II. After 28 days, 60.8% of the patients had an Oxford score of 0 or I; a significant mean improvement in the score of 0.97±0.86 (P<0.001) from 2.20±0.44 at day 1 to 1.23±0.88 at day 28 was observed. Tear break-up time and Schirmer scores had significantly improved while the number of patient-reported symptoms had significantly decreased (all P≤0.010). A large majority of patients still had a few spots on their naso-bulbar conjunctiva (86.1%), temporal-bulbar conjunctiva (81.4%) and cornea (84.7%). The investigators considered that DED had improved in 71.6% of the patients. Patients appreciated the eye drops for their efficacy and good tolerance profile, leading to a decreased use of artificial tears. No changes in intraocular pressure and visual acuity were observed; glycyrrhizin 2.5% eye drops were safe, with only one patient reporting a moderate, transient treatment-related contact allergy leading to the withdrawal of the patient. Overall, two patients reported three adverse events, two (moderate contact allergy in both eyes) were related to the eye drops and experienced by the same patient; treatment was stopped; the third event was not treatment-related.Conclusion: In this pilot study, glycyrrhizin 2.5% eye drops were well tolerated and provide a good clinical benefit to patients with moderate DED after 28 days of continued daily use. Keywords: dry eye disease, hyaluronic sodium, glycyrrhizin, inflammation, ocular lesions